The Influence Of Beauty Vlogger And Lifestyle On Wardah Cosmetic Purchasing Decisions On Tokopedia E-Commerce (Survey on Female Students in Tasikmalaya City) - Andriyani, Dewi; Lestari, Suci Putri; Arif (CV. Utami, 2024)
This research aims to determine the influence of Beauty Vlogger and Lifestyle on Wardah Cosmetics Purchasing Decisions on Tokopedia E-Commerce. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Beauty Vlogger and Lifestyle simultaneously have a positive and significant effect on purchasing decisions. Beauty Vlogger partially has a significant influence on purchasing decisions. Lifestyle partially has a significant effect on purchasing decisions.